User groups in action the management of user inputs in the NPD process - Tomes, Anne; Armstrong, Peter; Clark, Murray
This paper describes, through a case study of a small software company, an instance of the successful employment of user groups as a medium of design. Our work indicates that effective user groups require the product development manager to accomplish a number of relatively distinct social processes. These include establishing trust and credibility, managing expressions of user need, and involving users in the new product development process by enlisting them as designers. The implications of the findings are that participative models of the design process make demands on the social skills of product development managers which need to be addressed in their education and subsequent career development.
Another case study describes a small software company where the product development manager uses his social skills in employing user groups to improve design processes for new product development.
Keywords: User groups; User inputs